SUBOPTIMUM NONLINEAR CONTROL BY OPERATION SPEED CRITERION BASED ON BELLMAN-LYAPUNOV METHOD - Kudin, V. F.; Kolesnichenko, S. P. (Radio Electronics, Computer Science, Control, 2011)
A general-theoretical task of suboptimal nonlinear control algorithm synthesis is discussed. As an example, a two-mass electromechanical control system of a crane moving mechanism is examined taking into account load oscillations damping. The task is solved on the basis of Bellman–Lyapunov method using the concept of «invariant immersion» by operation speed criterion. The dynamics of a closed-loop system with a synthesized suboptimal regulator is investigated.